Carbon Dots–Implanted Graphitic Carbon Nitride Nanosheets for Photocatalysis: Simultaneously Manipulating Carrier Transport in Inter‐ and Intralayers. Issue 4 (3rd April 2020) - Han, Mei; Lu, Siyu; Qi, Fei; Zhu, Shoujun; Sun, Haizhu; Yang, Bai
Abstract : Se‐Chaperoned Synthesis In article number 1900517, Haizhu Sun, Bai Yang, and co‐workers prepare carbon dots‐implanted graphitic carbon nitride nanosheets (CCNS) via a one‐step Se‐chaperone method. Electronic structure modulation and heterostructure construction are achieved. Notably, the CCNS exhibit enhanced photocatalytic performance of CO2 reduction, water splitting for H2 production, and RhB degradation. There is great potential in synchronous energy conversion and environmental remediation.